Penerapan Metode Contextual Teaching and Learning Untuk Peningkatan Hasil Pembelajaran Bahasa Inggris - Langkameng, Oce Antipas (Universitas Persatuan Guru 1945 NTT, 2020)
In the learning process that took place in the school, there were generally many problems, including the old paradigm of learning activities, the learning approach used by teachers, less involving students and the use of resources and the medium of learning is minimal creativity. But this can result in not supporting the learning process and not achieving the learning objectives to the fullest. As is the case with the study of English at school, generally not attractive, as a result many learners who are less interested in learning English. The research aims to increase the students' participation in learning English. The type of this research was Classroom Action Research (CAR) using a qualitative approach with the planning, action, observation, and reflection phases. Prior to the implementation of the research, pre-action. Further research is conducted in two cycles, each cycle consists of three times the meeting. The subject of the research was a grade VII students of SMP Negeri 1 Kupang in the school year 2018/2019. The data were collected by observations, documentation, and recording, which were analyzed in a descriptive analytics. The result shows that the Contextual Teaching and Learning method can improve the learning outcome of grade VII the students of SMP Negeri 1 Kupang in the school year 2018/2019.